Physical activity as part of therapy of spondyloarthropathy - review - Mikołajczak, Karolina; Ćwirko, Hanna; Garlak, Urszula (Quality in Sport, 2025)
Spondyloarthropathy is a group of chronic inflammatory diseases involving the sacroiliac joints and spine. Due to the prevalence of spinal pain, its diagnosis is often delayed for up to several years. If left untreated, it leads to a significant deterioration of the patient's quality of life, disability, and eventually premature death. At present, there are drugs with which the disease activity can be effectively controlled, although some of them are not widely used due to their high cost. Despite the development of modern technology and the increasing spectrum of available therapies, rehabilitation and exercise still remain one of the basic elements of treatment. This article discusses and evaluates various forms of physical activity in terms of their effects on disease activity, joint and non-joint complaints, inflammatory markers and patient well-being. The most important conclusion of the analysis is that physical activity is safe for patients and it is never too late to start.